Perancangan Modul Penggajian Berbasis Odoo - Koeswanto, Vincent K. Edison; Yulia, Yulia; Adipranata, Rudy (Jurnal Infra, 2016)
Human Resource Module is one of the modules owned by Odoo. One of the feature of this module is payroll. However, the features is not in accordance with the needs of companies in Indonesia in general. This causes the payroll system in Odoo not suitable to be implemented directly in the company.To solve these problems, author develop the payroll system in Human Resource module in Odoo. The development of this system is preceded by designing and analyze the payroll system at PT X. It also conducted a review of the Act and other regulations relating to payroll system in Indonesia.The end result of this development are additional features and adjustment on payroll. The testing is done by implementing this system in company X.